A Comparison of Test Anxiety Between Normal Students and Students With Learning Disorders in Lordegan County During Academic Year 2015-2016 - Reza Heidari-Soureshjani; Farnaz Kargaran Dehkordi; Tayeb Mohammadi (Shahrekord University of Medical Sciences, 2018)
Background and aims: Anxiety can be defined as a state of fear and worry. Test anxiety is one of the students' constant fears that produces destructive and negative effects on students' educational performance and mental condition. There is not an exception among students with learning disorders and they all experience such type of anxiety. Therefore, in this research the test anxiety was compared in these two mentioned types of students. Methods: The present analytical-descriptive study was conducted on a sample of 129 students composed of 86 normal and 43 cases with learning disorders in Lordegan county. The cases were selected by simple random sampling and Sarason Anxiety Questionnaire was used for gathering data and finally the collected data was analyzed via analysis of covariance (ANCOVA) and SPSS 16.0. Results: The mean of anxiety level among students with learning disorders was 24.21 (±4.33) and 20.65 (±6.81) before and after the test respectively, and the measured mean for normal students was 18.52 (±5.56) before the test and 16.7 (±5.47) after the test. This result showed a significant difference between these two types of students (P<0.001), but there were no significant differences between control and test groups' sex and anxiety level (P>0.05). Conclusion: In these 2 studied groups, the test anxiety was decreased sharply after the test in comparison with that before it. As well, it was concluded that the normal students' anxiety was less than the anxiety of students with learning disorders in both phases.